La judicialización de los procesos de descentralización y autonomía. el caso del tribunal constitucional español y el desarrollo autonómico - Bercholc , Jorge O. (2016)
The theoretical and ideological substratum to give support to a process of decentralization, is changed and presents contradictory shades. The constitutional model of “integrated” federalism, with many concurrent competences, does that they are more diffuse generating conflicts for the delimiting of the same ones. In the Spanish case the TC must assume an intense activity and a very active, major role of the one that generally must assume a high court, to solve conflicts of competence in federations of “dualistic” model. The dispersion of opinions and approaches of the doctrine require to produce objective, rigorous and microscopic knowledge, which allows to approach at the process and to understand it with more sophistication, not only from positions, in excess, “general practitioners”